Indebtedness of households: changing characteristics - Rao, K.S. Ramachandra; Tripathi, A.K. (2001)
This paper attempts to examine indebtedness of rural and urban households in terms of their major characteristics in 1981 and 1991. The important changes introduced in the All-India Debt and Investment Survey of 1991-92 are reviewed and a comparison of the estimates of household debt from the survey with those derived from other sources is presented. - Reproduced
Keywords: Households - India; Debts